Selected cases of failure analysis and the regulatory agencies in Brazil. Part 2: Electric energy and oil. (May 2019) - Azevedo, C.R.F.; Feller, A.H.
Abstract: Two cases of failure analysis (thermoelectric turbine blades and crude oil pipeline) were selected to compile a brief study of the transparency of their respective regulatory agencies in Brazil. The transparency of the Brazilian Electricity Regulatory Agency (ANEEL) in terms of public access to both the investigation reports of accidents (thermoelectric generation and electricity distribution) and their regulatory actions is seen as inadequate. The transparency of Brazil's National Agency of Petroleum, Natural Gas and Biofuels (ANP) in terms of public access to both the investigation reports of serious pipelines accidents and their regulatory response is interpreted as unsatisfactory. The transparency of information plays an important role in the trade-off between the independence and the political control of the regulatory agencies. The regulatory agency for the mining industry (ANM) was briefly criticized in view of another recent collapse of an upstream tailing dam in the State of Minas Gerais, which caused the death of at least 142 people. In this sense, the publication of failure analysis cases and general access to these reports are valuable tools to improve the impact the regulatory agencies have on the general welfare of the country, as long as these reports are actually used to improve the effectiveness of these agencies. Highlights: Two cases of failure analysis (turbine blades and oil pipeline) were reviewed. These cases were used for a brief study of these regulatory agencies in Brazil. The transparency of these agencies to the investigation of these failures is discussed. The transparency of the regulatory actions to these failures is discussed.